1999
DOI: 10.1200/jco.1999.17.7.2190
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and Paclitaxel: Pharmacokinetic and Pharmacodynamic Interactions in Patients With Non–Small-Cell Lung Cancer

Abstract: Gemcitabine and paclitaxel pharmacokinetics were related to the percentage decrease in platelets. Paclitaxel did not affect the pharmacokinetics of gemcitabine, nor did gemcitabine affect the pharmacokinetics of paclitaxel, but paclitaxel increased dFdCTP accumulation. This might enhance the antitumor activity of gemcitabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 24 publications
7
78
0
Order By: Relevance
“…Furthermore, fluvastatin has been safely administered at high doses in paediatric patients with cancer (Lopez-Aguilar et al, 1999). Indeed, micromolar concentrations of gemcitabine and fluvastatin have been reached in human plasma in pharmacokinetic studies (Kroep et al, 1999;Kantola et al, 2000), and these plasma levels are in the range of the antiproliferative activity found in the present study. Moreover, the administered fluvastatin dose in our in vivo experiment was based on the study by Ferrara et al (2003), who showed, for the same total dose given in 14 days, serum concentrations of fluvastatin in mice higher than 1.2 mg ml À1 , representing drug levels of B2 times the mean drug concentration in human plasma after a 40 mg oral dose and confirming the potential translation to the clinic of our data.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, fluvastatin has been safely administered at high doses in paediatric patients with cancer (Lopez-Aguilar et al, 1999). Indeed, micromolar concentrations of gemcitabine and fluvastatin have been reached in human plasma in pharmacokinetic studies (Kroep et al, 1999;Kantola et al, 2000), and these plasma levels are in the range of the antiproliferative activity found in the present study. Moreover, the administered fluvastatin dose in our in vivo experiment was based on the study by Ferrara et al (2003), who showed, for the same total dose given in 14 days, serum concentrations of fluvastatin in mice higher than 1.2 mg ml À1 , representing drug levels of B2 times the mean drug concentration in human plasma after a 40 mg oral dose and confirming the potential translation to the clinic of our data.…”
Section: Discussionsupporting
confidence: 56%
“…For gemcitabine, the mean C max value of 37 AE 23 lg/mL was slightly higher than literature suggests, but occurred between 15 and 30 minutes after the start of infusion as expected. 23,24 The averages for AUC (0-t) of 18.7 AE 11.1 lg/hour/mL and AUC (inf) of 19.0 AE 11.3 lg/ hour/mL were also slightly higher than the reported values; this was likely because of the higher C max values. However, gemcitabine decreased below quantifiable levels after 2 hours (mean t 1/2 of 0.3 AE 0.1 hours), and there was no evidence of gemcitabine after 24 hours in any of the patients sampled.…”
Section: Correlative Studiesmentioning
confidence: 50%
“…The t 1/2 was determined to be 8.4 AE 1.3 hours, compared with literature containing individual values ranging from 5 to 16 hours. 23,24 The mean total AUC for irinotecan was calculated as 5640 AE 996 ng/hour/mL, and mean clearance was 33.5 AE 7.2 L/hour. The mean total AUC for the major metabolite SN38 was determined to be 295 AE 68 ng/hour/mL.…”
Section: Correlative Studiesmentioning
confidence: 99%
“…This approach is supported by the lack of pharmacokinetic interaction between the two drugs and the ability of paclitaxel to increase cellular accumulation of gemcitabine triphosphate (dFdCTP), the active metabolite of gemcitabine, with the possibility of enhancing its antitumor activity (Kroep et al, 1999). Several phase I studies involving different schedules of paclitaxel and gemcitabine in a variety of tumour types have been encouraging and mainly found neutropenia and elevated transaminase levels to be dose-limiting (Poole et al, 1997;Sandler et al, 1997).…”
mentioning
confidence: 99%
“…Preliminary data revealed that among the first 30 patients enrolled, dose escalation was well tolerated and the response rate was 30%; any failure to undergo dose escalation was mainly unrelated to adverse effects. This schedule was also investigated in a phase I/II study of the pharmacokinetic and pharmacodynamic interactions between gemcitabine and paclitaxel in patients with NSCLC (Kroep et al, 1999). Due to mild toxicity, the dose of paclitaxel was increased from 150 to 200 mg/m 2 .…”
mentioning
confidence: 99%